Agro-Technopreneurship di Era Artificial Intelligence: Menjembatani Inovasi Digital, Produktivitas, dan Keberlanjutan Pertanian - Nugrahini Susantinah Wisnujati; Dewa Oka Suparwata; Suherlan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to comprehensively examine the role of agro-technopreneurship in the era of Artificial Intelligence in bridging digital innovation, productivity improvement, and agricultural sustainability. This research employed a literature review method with a qualitative approach. The data was obtained from Google Scholar for the period 2014–2026. Of the 50 articles identified, 33 were selected based on their relevance to the study. The data analysis technique used descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The findings indicate that entrepreneurship education plays an important role in shaping innovative mindsets and technological adaptability, the development of superior human resources enhances analytical capacity and productivity, AI-based digital innovation accelerates efficiency and the transformation of agricultural business models, while sustainability ensures a balance between economic, social, and environmental aspects. The integration of these four aspects creates a synergy that strengthens the competitiveness of agro-technopreneurship in facing global challenges. The limitation of this study lies in the use of a literature review method, which does not provide an in-depth representation of empirical conditions and variations in local contexts. Further research is recommended to employ empirical studies and an integrative model of agro-technopreneurship so that the relationships between variables can be tested in a more contextual and measurable manner